An ecological, environmental, and economic indicators-based approach towards enhancing sustainability in water and nutrient use for passion fruit cultivation in Colombia - Sonia Mercedes Polo-Murcia; Nesrine Chaali; Camilo Ignacio Jaramillo-Barrios; Sofiane Ouazaa; Victor Javier Polo; John Edisson Calderon Carvajal (Environmental and Sustainability Indicators)
Yellow passion fruit is a tropical crop of significant economic importance in Colombia. Efficient irrigation and fertilization strategies can enhance soil health, reduce environmental impact, and boost crop profitability. However, their application to passion fruit remains underexplored. This study evaluated the combined effects of 3 irrigation levels (I1: 48%, I2: 43%, I3: 33% of field capacity) and 3 fertilization strategies (F1: 100% synthetic, F2: organic + synthetic, F3: synthetic + biofertilizer) across two harvest periods (HP1 and HP2), using an ecological and environmental indicators-based approach. Principal component analysis (PCA) was used to determine optimal irrigation and fertilization practices. Mixed linear models were applied to compare ecological and economic indicators. In HP1, significant interactions (p ≤ 0.01) influenced yield, with I2F1 achieving the highest net ecosystem economic benefits (NEEB) (31.47 ± 1.82 thousand USD ha⁻1, p < 0.01), yield (18.49 ± 1.00 t ha⁻1), and irrigation water use efficiency (IWUE: 7.60 ± 0.41 kg m⁻³). Fertilization with F2 under I2 maximized nutrient use efficiency (PFPN: 223.88 ± 11.75 kg kg⁻1, PFPK: 675.97 ± 35.48 kg kg⁻1).In HP2, I2F3 achieved the highest NEEB (27.42 ± 0.70 thousand USD ha⁻1) and yield (16.55 ± 0.39 t ha⁻1), while I2F2 exhibited high IWUE (2.02 ± 0.12 kg m⁻³) and consistent nutrient use efficiency (PFPN: 566.06 ± 33.85 kg kg⁻1; PFPK: 1658.65 ± 99.19 kg kg⁻1). F2 demonstrated strong economic performance, supported by a PCA, explaining over 83% of the variance in both periods. I2F2 achieved the highest integrated scores (2.488 in HP1; 1.047 in HP2). I2 combined with F2 led to optimized yield, profitability, and sustainability by minimizing resource waste and economic risks. These findings highlight the potential of resource-efficient practices for sustainable tropical agriculture.